Implementasi Peraturan Daerah Kabupaten Gresik Nomor 23 Tahun 2004 tentang Retribusi Izin Mendirikan Bangunan (Studi pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu Kabupaten Gresik) - Arundinasari, Indira; Makmur, Mohamad; Wanto, Alfi Haris (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Regional Autonomy makes Regional Income as a financial source for the management of its own area so as to minimize dependence on the central government is a requirement in the state government system. Sources of Income are derived from Regional Taxes; regional retribution; results of management of separate regional wealth and others legitimate local revenues. Law No. 28 of 2009, the definition of regional retribution, is building permit levies as payment for services or the granting of certain permits specifically provided and/ or given by local governments for the benefit of individuals or entities, this is regulated in Gresik Regency Regulation Number 23 of 2004 about Building Permit Levy so that it is expected that there will be an increase in Regional Original Income from the regional levies licensing sector managed by DPM-PTSP as a government agency that is responsible for implementing the Regional Levies licensing policy for building construction.